Immediate and Sustained Effect of Neonatal Teaching in a Perinatal Setting in Urban Laos - Hoehn, Thomas; Genet, Petra; Balan, Percy; Schramm, Dirk; Verde, Pablo Emilio; Phengsavanh, Alongkone (American Journal of Perinatology, 2020)
Objective This study aimed to quantify knowledge on neonatal topics among obstetricians and pediatricians participating in a perinatal teaching program aimed at reducing neonatal mortality in Laos.Study Design Obstetricians and pediatricians from Vientiane and the surrounding areas participated in a 1-week teaching program in obstetric and neonatal topics and responded to pre- and posttests questionnaires to quantify their knowledge.Results Although questions were predominantly related to neonatal topics, obstetricians performed significantly better than pediatricians during the pretest. Both groups increased their knowledge significantly as quantified by the results of the posttest.Conclusion The teaching program was effective in improving knowledge on perinatal mortality related topics of the participants. These results may be related to the fact that most of the obstetricians had participated in a structured teaching program previously, whereas the pediatricians did not. We thus speculate that there is a sustained effect of even a 1-week teaching program in neonatology even several years after the initial teaching.
Keywords: postgraduate teaching; obstetricians; pediatricians; pretest; posttest